Oxidoreductase from `Alphonso' mango catalyzing biosynthesis of furaneol and reduction of reactive carbonyls - Kulkarni, Ram; Chidley, Hemangi G.; Deshpande, Ashish; Schmidt, Axel; Pujari, Keshav; Giri, Ashok P.; Gershenzon, Jonathan; Gupta, Vidya (SpringerPlus, 2013)
Two furanones, furaneol (4-hydroxy-2,5-dimethyl-3(2H)-furanone) and mesifuran (2,5-dimethyl-4-methoxy-3(2H)-furanone), are important constituents of flavor of the Alphonso cultivar of mango (Mangifera indica). To get insights into the biosynthesis of these furanones, we isolated an enone oxidoreductase gene from the Alphonso mango. It has high sequence similarity to an alkenal/one oxidoreductase from cucumber (79% identity) and enone oxidoreductases from tomato (73% identity) and strawberry (72% identity). The complete open reading frame was expressed in E. coli and the (his) 6-tagged recombinant protein was purified by affinity chromatography. The purified protein assayed with NADH as a reducing agent converted D-fructose-1,6-diphosphate into furaneol, the immediate precursor of mesifuran. The enzyme was also able to convert two highly reactive carbonyls, 3-buten-2-one and 1-penten-3-one, produced by lipid peroxidation in plants, into their saturated derivatives. Expression profiling in various ripening stages of Alphonso fruits depicted an expression maxima at 10 days after harvest stage, shortly before the appearance of the maximum amount of furanones (completely ripe stage, 15 days after harvest). Although no furanones were detected at the 0 day after harvest stage, significant expression of this gene was detected in the fruits at this stage. Overall, the results suggest that this oxidoreductase plays important roles in Alphonso mango fruits.
Keywords: Detoxification; Enone oxidoreductase; Flavor; Mangifera indica; Ripening

New insight into sugarcane industry waste utilization (press mud) for cleaner biobutanol production by using c. acetobutylicum nrrl b-527 - Nimbalkar, Pranhita R.; Khedkar, Manisha A.; Gaikwad, S. G.; Chavan, Pramod V.; Bankar, Sandip B. (Applied Biochemistry and Biotechnology, 2017)
In the present study, press mud, a sugar industry waste, was explored for biobutanol production to strengthen agricultural economy. The fermentative production of biobutanol was investigated via series of steps, viz. characterization, drying, acid hydrolysis, detoxification, and fermentation. Press mud contains an adequate amount of cellulose (22.3%) and hemicellulose (21.67%) on dry basis, and hence, it can be utilized for further acetone-butanol-ethanol (ABE) production. Drying experiments were conducted in the temperature range of 60–120 °C to circumvent microbial spoilage and enhance storability of press mud. Furthermore, acidic pretreatment variables, viz. sulfuric acid concentration, solid to liquid ratio, and time, were optimized using response surface methodology. The corresponding values were found to be 1.5% (v/v), 1:5 g/mL, and 15 min, respectively. In addition, detoxification studies were also conducted using activated charcoal, which removed almost 93–97% phenolics and around 98% furans, which are toxic to microorganisms during fermentation. Finally, the batch fermentation of detoxified press mud slurry (the sample dried at 100 °C and pretreated) using Clostridium acetobutylicum NRRL B-527 resulted in a higher butanol production of 4.43 g/L with a total ABE of 6.69 g/L. © 2017 Springer Science+Business Media New York Author keywords
Keywords: Acetone; Acetone butanol ethanols; Acidic pre treatments; Agriculture; Biobutanol; cellulose; Clostridium acetobutylicum; Detoxification; Drying; Drying Fermentation; FermentationSpoilage; Fermentative production; Pre-treatment; Press mud; Press mud Pretreatment; Response surface methodology; Sugar industry; Sulfur determination

Glucosinolate induces transcriptomic and metabolic reprogramming in Helicoverpa armigera - Jagdale, Shounak; Tellis, Meenakshi; Barvkar, Vitthal T.; Joshi, Rakesh S. (3 Biotech, 2021)
Glucosinolates protect plants from herbivory. Lepidopteran insects have developed resistance to glucosinolates which is well studied. However, the molecular effects of glucosinolate intake on insects are unexplored. To elucidate this, we performed transcriptomics and metabolomics of sinigrin-fed Helicoverpa armigera. Transcriptomics exhibits significant dysregulation of 2375 transcripts, of which 1575 are upregulated and 800 downregulated. Gene Ontology analysis of differentially expressed genes reveals that key hydrolases, oxidoreductases, and transferases are majorly affected. The negative impact of sinigrin is significant and localized in the endomembrane system and mitochondria. It also disturbs various biological processes such as regulation of protein metabolism and cytoskeletal organization. Furthermore, H. armigera putative myrosinase-like enzymes may catalyze the breakdown of sinigrin to allyl isothiocyanate (AITC). AITC targets the electron transport chain causing oxidative stress. KEGG pathway enrichment shows significant upregulation of oxidative phosphorylation, glutathione metabolism and amino acid metabolism. Activation of these pathways induces glutathione synthesis for sinigrin detoxification. Differential gene expression indicates upregulation of glutathione S-transferase and succinate dehydrogenase suggesting mitochondrial impact. Transcriptomics data correlated with metabolomics show changes in serine, methionine, ornithine, and other metabolite levels. It corroborates well with the transcript alterations supporting the increased glutathione production. Thus, our data suggest that sinigrin generates oxidative stress in H. armigera and insects alter their metabolic wiring to overcome sinigrin-mediated deleterious effects.
Keywords: Detoxification; Glucosinolate; Glutathione; mitochondria; Oxidative stress

Glycosyltransferases: the multifaceted enzymatic regulator in insects - Nagare, M.; Ayachit, M.; Agnihotri, A.; Schwab, W.; Joshi, R. (Insect Molecular Biology, 2021)
Glycosyltransferases (GTs) catalyse the reaction of glyco-conjugation of various biomolecules by transferring the saccharide moieties from an activated nucleotide sugar to nucleophilic glycosyl acceptor. In insects, GTs show diverse temporal and site-specific expression patterns and thus play significant roles in forming the complex biomolecular structures that are necessary for insect survival, growth and development. Several insects exhibit GT-mediated detoxification as a key defence strategy against plant allelochemicals and xenobiotic compounds, as well as a mechanism for pesticide cross-resistance. Also, these enzymes act as crucial effectors and modulators in various developmental processes of insects such as eye development, UV shielding, cuticle formation, epithelial development and other specialized functions. Furthermore, many of the known insect GTs have been shown to play a fundamental role in other physiological processes like body pigmentation, cuticular tanning, chemosensation and stress response. This review provides a detailed overview of the multifaceted functionality of insect GTs and summarizes numerous case studies associated with it.
Keywords: Allelochemicals; Detoxification; Development; glycosyltransferases (GTs); insects

Process development for crystalline xylitol production from corncob biomass by Pichia caribbica - Dasgupta, Diptarka; Sidana, Arushdeep; Sarkar, Bipul; More, Snehal; Ghosh, Debashish; Bhaskar, Thallada; Ray, Anjan (Food and Bioproducts Processing, 2022)
Xylitol, a commodity chemical, is widely used in nutraceutical and pharmaceutical formulations. Microbial xylitol production is a promising alternative to mitigate current industrial practice issues and offers an environment-friendly sustainable conversion route. This study demonstrates a bioprocess for xylitol production from corncob using a mesophilic yeast Pichia caribbica. Corncob was hydrolyzed by dilute acid and steam explosion to recover fermentable xylose and used as the feed for xylitol production. Activated carbon treatment (3% w/v) completely removed the biomass-derived inhibitors furfural and hydroxymethyl furfural from the liquid hydrolysate. The fermenting yeast Pichia caribbica produced 124.1 +/- 0.45 g/L xylitol from the detoxified and concentrated corncob hydrolysate with a high yield of 0.80 +/- 0.02 g/g. The crystallized xylitol with 96.5% purity demonstrated no harmful effects on the cell line used as a control for the in-vitro toxicity studies. This proof of concept can be applied to help scale up for bio-refinery-based large-scale production of xylitol from corncob biomass.(c) 2022 Institution of Chemical Engineers. Published by Elsevier Ltd. All rights reserved.
Keywords: Biomass; Corncob; Detoxification; Fermentation; Toxicity analysis; xylitol

Process development for detoxification of corncob hydrolysate using activated charcoal for xylitol production - Ahuja, Vishal; Kshirsagar, Siddheshwar; Ghosh, Prasenjit; Sarkar, Bipul; Sutar, Ajit; More, Snehal; Dasgupta, Diptarka (Journal of Environmental Chemical Engineering, 2022)
The work describes process development for detoxification of corncob hydrolysate using activated carbon for microbial xylitol production. Activated carbon was used as an adsorbent to completely remove the major fermentation inhibitors obtained during dilute acid and steam explosion of biomass. A xylitol yield of 0.78 g/g was achieved from the detoxified hydrolysate in a 5 L fermenter by Pichia caribbica. The spent carbon was effectively regenerated and used for three consecutive cycles of operation. The successive regeneration and reuse of carbon could reduce the operational cost by similar to 38% and be used as a reference dataset for process scale-up and cost-effective xylitol production.
Keywords: Activated charcoal; Detoxification; Fermentation; Regeneration; xylitol

Stacking herbicide detoxification and resistant genes improves glyphosate tolerance and reduces phytotoxicity in tobacco (Nicotiana tabacum L.) and rice (Oryza sativa L.) - Vennapusa, Amaranatha Reddy; Agarwal, Subham; Hm, Hanumanth Rao; Aarthy, Thiagarayaselvam; Babitha, K. C.; Thulasiram, V. Hirekodathakallu; Kulkarni, Mahesh J.; Melmaiee, Kalpalatha; Sudhakar, Chinta; Udayakumar, M.; Vemanna, Ramu S. (Plant Physiology and Biochemistry, 2022)
Glyphosate residues retained in the growing meristematic tissues or in grains of glyphosate-resistant crops affect the plants physiological functions and crop yield. Removing glyphosate residues in the plants is desirable with no penalty on crop yield and quality. We report a new combination of scientific strategy to detoxify glyphosate that reduces the residual levels and improve crop resistance. The glyphosate detoxifying enzymes Aldo-keto reductase (AKR1) and mutated glycine oxidase (mGO) with different modes of action were co-expressed with modified EPSPS, which is insensitive to glyphosate in tobacco (Nicotiana tabacum L.) and rice (Oryza sativa L.). The transgenic tobacco plants expressing individual PsAKR1, mGO, CP4-EPSPS, combinations of PsAKR1:CP4EPSPS, PsAKR1:mGO, and multigene with PsAKR1: mGO: CP4EPSPS genes were developed. The bio-efficacy studies of in-vitro leaf regeneration on different concentrations of glyphosate, seedling bioassay, and spray on transgenic tobacco plants demonstrate that glyphosate detoxification with enhanced resistance. Comparative analysis of the transgenic tobacco plants reveals that double and multigene expressing transgenics had reduced accumulation of shikimic acid, glyphosate, and its primary residue AMPA, and increased levels of sarcosine were observed in all PsAKR1 expressing transgenics. The multigene expressing rice transgenics showed improved glyphosate resis-tance with yield maintenance. In summary, results suggest that stacking genes with two different detoxification mechanisms and insensitive EPSPS is a potential approach for developing glyphosate-resistant plants with less residual content.
Keywords: Detoxification; Gene stacking; Glyphosate; Herbicide; Multigene; Residual toxicity; Resistant; rice; Tobacco; Transgenics